Histone deacetylase inhibition modulates histone acetylation at gene promoter regions and affects genome-wide gene transcription in Schistosoma mansoni - Anderson, Letícia; Gomes, Monete Rajão; daSilva, Lucas Ferreira; Pereira, Adriana da Silva Andrade; Mourão, Marina M.; Romier, Christophe; Pierce, Raymond; Verjovski-Almeida, Sergio (PLOS Neglected Tropical Diseases, 2017)
Author summary Human schistosomiasis is a disease caused by the parasite Schistosoma spp. that affects over 230 million people worldwide. Treatment depends on a single drug, praziquantel, and the search for new drugs calls for exploiting strategies that are successful for other pathologies such as cancer, including the test of inhibitors targeting chromatin enzymes responsible for modifying histone proteins associated with DNA. Histone modifications regulate cellular gene expression. Inhibitors targeting an important class of these histone-modifying enzymes, namely Histone Deacetylases (HDACs), are known to induce in vitro mortality of the parasite (at the schistosomula and adult worm stages), however the molecular changes caused in the parasite were not known. In this scenario, we studied the effect of the HDAC inhibitor Trichostatin A on the parasite genome-wide gene expression, on histone modifications at gene promoter regions and on the chromatin acetylation status, and found important affected gene pathways. In addition, this approach showed affected genes associated with other histone modifications, which led us to test and identify a synergistic schistosomicidal agent, GSK343, an EZH2 histone methyltransferase inhibitor. Our work points to the class of histone methyltransferase modifying enzyme as a novel drug target to be explored in the future for parasitosis treatment.